Associations Between ANC History, Anemia, Exclusive Breastfeeding, and Maternal Diet with Nutritional Status of Children Aged 2–5 in Rural Indonesia - Langi, Louisa Ariantje; Prihantini, Nur Nunu; Indah, Louise Kartika (The Indonesian Institute of Science and Technology Research, 2025)
The first thousand days of life, beginning with pregnancy, are crucial for a child's development, influenced by factors like maternal nutrition, health, antenatal care (ANC), exclusive breastfeeding, birth weight, immunization, and complementary feeding. Regular ANC visits are vital for monitoring the health of both mother and fetus. This cross-sectional study examined the association between ANC history, anemia during pregnancy, exclusive breastfeeding, and maternal dietary practices with child nutritional status in Ciranggem Village, Sumedang Regency (2021–2023). Data from 30 mothers of children aged 2–5 years were analyzed using Chi-square tests. Significant associations (p < 0.05) were found between all four maternal factors and child nutritional outcomes, highlighting their collective impact on growth. The study used an analytical observational design with total sampling. Results showed 73.3% of mothers received ANC, practiced exclusive breastfeeding, and maintained a healthy diet, while 26.7% had a history of anemia. Children's nutritional status was as follows: Normal (66.7%, 20 children), Stunting (20%, 6 children), Underweight (10%, 3 children), and Overweight (3.3%, 1 child). Statistical analysis yielded a p-value < 0.05, indicating a significant link between maternal factors and child nutrition.